Effect Of Service Quality And Price Perception On Customer Satisfaction And Its Impact On Customer Loyalty (Case Study At Po Sudiro Tungga Jaya) - Laksono, Gigih Andi; Hannan, Sufrin; Farradia, Yuary (UNIVERSITAS PAKUAN, 2024)
PO Sudiro Tungga Jaya is one of the inter-city bus transportation companies located at Jl. Raya Solo No. 123 Suratmajan, Maospati, Magetan, East Java. One form of success of a company lies in customer satisfaction and loyalty. There are several factors that influence customer satisfaction and loyalty such as service quality and price perception. The method used is a type of verification research with explanatory survey research methods. The research technique used is a questionnaire. The type of data used is quantitative. The sampling method is nonprobability sampling with purposive / judging sampling method using customers as a sample, namely 100 respondents. The analysis method used is descriptive statistics. The results showed that service quality, price perception and customer satisfaction have an impact on loyalty both directly and indirectly.